Unexpected role of prefactors in defects diffusion: The case of vacancies in the 55Fe-28Ni-17Cr concentrated solid-solution alloys. (15th September 2022) - Sauvé-Lacoursière, Alecsandre; Gelin, Simon; Adjanor, Gilles; Domain, Christophe; Mousseau, Normand
Abstract: Variations in diffusion rates of simple point defects, such as vacancies and interstitials, are generally assumed to be dominated by energy barriers, as demonstrated for example by the large number of kinetic Monte Carlo studies that rest on constant rate prefactors. While this is mostly correct when energy barriers are well separated from each other, typically in crystals, entropic variations between the local minima and associated activated states become increasingly important as energy barriers of diffusion-mediating-mechanisms get closer, typically in disordered environments. The unexpected slower defect diffusion observed in high entropy alloys, which are characterized by the presence of a large number of different elements in roughly equal proportions, has brought us to revisit the role of prefactors. Combining the Activation-Relaxation Technique nouveau (ART nouveau) and the harmonic approximation for computing diffusion prefactors, we find that vacancy diffusion prefactors in a 55Fe-28Ni-17Cr concentrated solution alloy modeled with EAM empirical potentials can vary by up to six orders of magnitude, at almost constant energy barrier. This variation, mostly associated with changes in local pressure, suggests that prefactor could play a much more important role than previously thought in the defect kinetics of high entropy alloys and of disordered systems in general.